Situation of Elderly People Living in Old Age Home A Study of Gandaki Province - Thapa, Shrijana (Rural Development Journal, 2017)
The study is on the “Explaining the Situation of Elderly People Living in Old Age Home (A Study of Gandaki Province)” by the method of collecting tool. The main purpose of the study is to collected data form primary and if required secondary data has collected. Primary data has collected from all elderly people of aged 60+years at the old age home. From the lottery method researcher has taken western development region of Gandaki Province. Researcher has selected three districts viz. Kaski, Tanahun and Syanjga and three districts were excluded. The collection of the data procedure is based on personal interviews and the cross table. The main objective of this study is to be identify the socio economic and demographic characteristic of elderly people of old age home, analyzed the health status care facilities and utilization of elderly allowance provide by old age home, and to identify the reason of senior citizen going to old age home. This study has limited to the population who are 60 years above and some are excluded especially who are physically and mentally disable or who are unable give answers. The researcher shows that numbers of elderly women are high than elderly men. The highest elderly people age group is 70- 79 years. At the old age home Hindus are highest which is 94 percent and most of them are Brahmins which is 70 percent. Most of the elderly people are illiterate. Majority of widow/widower are high at old age home carrying 60 percent and rest of 17 percent are unmarried or who have no relatives. The proportion of time duration (5-10 years) of staying at old age home is high and the main reasons of joining old age home is the lack of rearing and caring person in their families, 63 percent are there because of death partner. Most of the times they want to spend their daily life time chatting with friends, doing religious activities, visiting the surrounding. Elderly people are facilitated with old aged allowance and single women/widow. They use it for own expenses such as medicine, food, and clothing. Most of the elderly people faced back pain, headache, swelling of legs, poor eyesight. Most of the elderly people are satisfied from old age home. Research shows that elderly people are satisfied from old age home; they get free treatment from government and some private provide free health camp. However, rooms are common and no attached bathroom but they have friendly environment.